The Development of Fourth Grade Primary School Science Learning Material Based on Local Wisdom at SDN Kesongo 01 Kabupaten Semarang - Asna, Sumilah, H. A. Zaenal Abidin, Afifah Nurul (Elementary School Teacher, 2017)
Based on the result of 2015 PISA (Programme for International Students Assessment) in term of science, Indonesia ranked 64th from 72 countries. Meanwhile based on the result of TIMSS (Trends in International Mathematics and Science Study), Indonesian ranked 45th from 48 countries. Those results showed that Indonesia still have low quality in science. This problem also happened in SDN Kesongo 01. It was known that students had low science learning outcome because learning material had not yet developed. In order to solve this problem, researcher developed an innovative learning material based on local wisdom. This research aimed to know the feasibility, students and teacher responses, and the effectiveness of 4th grade Primary School Science learning material based on local wisdom. This research was research and development (RD). Main subject of this research was students of class IV SDN Kesongo 01. Data analysis were percentage descriptive statistic, normality test, t-test and gain test. The results showed that 4th grade primary school science learning material based on local wisdom was developed by integrating the lesson material with the contents of local wisdom, feasible to be used, and effectively improved student learning outcome with moderate criteria. Showed by the result of gain test 0,6 and t test 0.00. The conclusions of this research were 4th grade primary school science learning material based on local wisdom was very feasible, obtained very positive responses, and effectively improved student learning outcome. Suggestion from this research was 4th grade primary school science learning material based on local wisdom can be used as an alternative learning material in science lesson in the accordance with the guideline.